Isolation of Bacillus cereus from botanical soil and subsequent biodegradation of waste engine oil - Bhurgri, Shazia; Talpur, Farah Naz; Nizamani, Shafi Muhammad; Afridi, Hassan Imran; Surhio, Muhammad Ali; Shah, Muhammad Raza; Bong, Chui Wei (Springer Verlag, 2018)
Waste engine oil causes a vital environmental pollution when it spill during change and transportation and products of waste engine oil causes lethal effects to the living systems. Thus, abiotic and biotic approaches are being extensively used for removal of waste engine oil pollution. Therefore in present study, waste engine oil degradation was accomplished by a new bacterial culture, isolated from the soil by an enrichment technique. Morphological, biochemical and gene sequence analysis revealed that isolate was Bacillus cereus. Subsequently, biodegradation potential of B. cereus for waste engine oil was studied. Experimental variables, such as pH, substrate concentration, inoculum size, temperature and time on the biodegradation, were checked in mineral salt medium. The biodegradation efficiency of B. cereus was determined by gravimetry, UV–visible spectrophotometry and gas chromatography. In addition, waste engine oil was also characterized by GC–MS and FTIR for its major constituents, which showed total 38 components in waste engine oil, including hopanes, benzopyrene, long-chain aliphatic hydrocarbons, dibenzothiophenes, biphenyl and their derivatives. Results of successive biodegradation indicated that B. cereus was capable to degrade 1% of waste engine oil with 98.6% degradation potential at pH 7 within 20 days. Hence, B. cereus presents an innovative tool for removing the engine oil from the contaminated area.